2014
DOI: 10.1111/gcbb.12221
|View full text |Cite
|
Sign up to set email alerts
|

Mineral soil carbon pool responses to forest clearing in Northeastern hardwood forests

Abstract: Harvesting forests introduces substantial changes to the ecosystem, including physical and chemical alterations to the soil. In the Northeastern United States, soils account for at least 50% of total ecosystem C storage, with mineral soils comprising the majority of that storage. However, mineral soils are sometimes omitted from whole-system C accounting models due to variability, lack of data, and sample collection challenges. This study aimed to provide a better understanding of how forest harvest affects mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Petrenko and Friedland (2014) found that average mineral soil C stocks were 34.9, 32.1, and 26.4 Mg ha −1 for 0-10, 10-20, and 20-30 cm depth increments in recently (<100 yr old) harvested stands across the northeastern USA. The corresponding C concentrations for these depth increments (7.2%, 4.6%, and 3.3%) were higher than our values, which may partially explain the lower mineral soil C stocks observed at our study site.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Petrenko and Friedland (2014) found that average mineral soil C stocks were 34.9, 32.1, and 26.4 Mg ha −1 for 0-10, 10-20, and 20-30 cm depth increments in recently (<100 yr old) harvested stands across the northeastern USA. The corresponding C concentrations for these depth increments (7.2%, 4.6%, and 3.3%) were higher than our values, which may partially explain the lower mineral soil C stocks observed at our study site.…”
Section: Discussionmentioning
confidence: 96%
“…This analysis indicated that the probability of detecting a significant treatment effect was only 6%. Other studies on soil C have also shown that their effect tests had low power due to low replication (McLaughlin and Phillips 2006;Kurth et al 2014;Petrenko and Friedland 2014). For example, Petrenko and Friedland (2014) found that between 60 and 230 stands meeting their study's criteria would be required to detect significant differences in mineral soil C pools depending on the depth increment sampled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have observed soil C release from certain horizons in temperate forest soils after harvest (Grand and Lavkulich, 2012;Nave et al, 2010). Studies specific to northern New England have observed C decreases in mineral soil horizons after clear cutting (Zummo and Friedland, 2011;Petrenko and Friedland, 2014).…”
mentioning
confidence: 99%